Analyses of research on the health of college students based on a perspective of knowledge mapping. (August 2016) - Zhang, C.; Zhang, J.; Long, C.; Zheng, J.; Su, C.; Hu, W.; Duan, Z.
Highlights: This research examines the knowledge structure of college students' health research by using knowledge mapping and co-occurrence word analysis. It showed the state of research on college students' health, current research focus as well as the directions in which it's developing and provide a basis of decision-making for future research. Research subjects on the health of college students have expanded extensively, as research content has become more concrete. Physical exercise, smoking and psychological health of college students have continued to attract the attention of researchers.